Study of Complications Associated With Acute Anterior Wall MI Presenting at a Tertiary Care Hospital - Shah, Sultan; Uddin, Jalal; Ur-Rehman, Fazal-; Hashim, Muhmmad; Mohammad Khan, Dost; Ali, Hikmat; ., Sanaullah; Ullah kakar, Sana (Biological and Clinical Sciences Research Journal, 2025)
Acute Anterior Wall Myocardial Infarction (AWMI) is a severe type of MI that frequently results in life-threatening complications and has a high morbidity and death rate. Objective: This study aims to assess the prevalence and types of complications associated with AWMI in patients admitted to tertiary care Hospitals in Quetta. Methodology: In a tertiary care hospital in Quetta, Pakistan, 200 AWMI patients participated in a qualitative study. Semi-structured interviews were used to gather data, and content analysis was used for analysis. Results: Twenty-four percent of patients had cardiogenic shock, and forty percent had arrhythmias, the most prevalent of which were atrial fibrillation (11%) and ventricular tachycardia (15%). 35% of patients experienced mechanical problems, most common being ventricular thrombus left (10%) and mitral regurgitation (15%). Conclusion: Significant consequences from AWMI necessitate early identification and treatment. Through effective treatment plans and ongoing monitoring, tertiary care facilities significantly contribute to better patient outcomes.